A participação do Conselho Popular de Saúde na dinâmica deliberativa do Conselho Municipal de Saúde de Diadema/SP: um processo em questão - 2008 - 2010 - Costa, Tânia da (2012)
This dissertation has as its object the participation of the CPS in the deliberative dynamics of the CMS of Diadema/SP, in the period from 2008 to 2010. The general objective of the research was to analyze the participation of the CPS in the deliberative dynamics of the CMS, aiming at understanding the nature and the extent of this institutionalized participation. The driving question was: how did the participation of the CPS in the deliberative dynamics of the CMS of Diadema in the period from 2008 to 2010 take place? Our hypothesis is that the participation of the CPS in the deliberative dynamics of the CMS is institutionalized, the councilors possessing political representativeness as a result of having been directly elected by the population, but also exhibiting liabilities related to their lack of technical qualifications on health issues and to their limited political protagonism, especially with regard to issues of autonomy and articulation with the powers of political and civil society. The basic conceptual references adopted State/Civil Society; health; participation and councils were fundamented mostly on contemporary Brazilian authors. The adopted methodology was that of qualitative research, consisting of a literature review in the areas of Sociology, Social Service, and Collective Health; documental research in the private archives of local leaders, in the Municipal Institute of Studies, in Diadema s municipal offices, among others; fieldwork, comprising the realization of semi-structured interviews with nine research subjects, those being: six CMS councilors, two former mayors and a long-standing leader in the health area. For the analysis of these data, the techniques of documental analysis and content analysis were used. The results of the research show, on the one hand, the relevance of the participation of the CPS in the deliberative dynamics of the CMS, due to the fact that the former s councilors are elected by the users of the healthcare system, and on the other hand, the liabilities of this participation, resulting from both the parallel institutionalization involving the CPS and the CMS and the councilors lack of technical qualifications and limitations in their political protagonism